Excitatory Dendritic Mitochondrial Calcium Toxicity: Implications for Parkinson’s and Other Neurodegenerative Diseases - Verma, Manish; Wills, Zachary; Chu, Charleen T. (Frontiers in Neuroscience, 2018)
Dysregulation of calcium homeostasis has been linked to multiple neurological diseases. In addition to excitotoxic neuronal cell death observed following stroke, a growing number of studies implicate excess excitatory neuronal activity in chronic neurodegenerative diseases. Mitochondria function to rapidly sequester large influxes of cytosolic calcium through the activity of the mitochondrial calcium uniporter (MCU) complex, followed by more gradual release via calcium antiporters such as NCLX. Increased cytosolic calcium levels almost invariably result in increased mitochondrial calcium uptake. While this compensatory response may limit classic excitotoxic injury in the short term, recent studies employing live calcium imaging and molecular manipulation of calcium transporter activities suggest that mitochondrial calcium overload plays a key role in Parkinson’s disease (PD), Alzheimer’s disease (AD), amyotrophic lateral sclerosis (ALS) and related dementias (PDD, DLB, FTD). Herein, we review the literature on increased excitatory input, mitochondrial calcium dysregulation, and the transcriptional or posttranslational regulation of mitochondrial calcium transport proteins, with an emphasis on the PD-linked kinases LRRK2 and PINK1. The neuroprotective effects of modulating MCU, NCLX and LETM1 are reviewed. We propose that the shortening and simplification of the dendritic arbor observed in neurodegenerative diseases occur through excitatory mitochondrial toxicity (EMT), which triggers mitophagy and perisynaptic mitochondrial depletion, mechanisms that are distinct from classic excitotoxicity.